2017
DOI: 10.1002/jsfa.8698
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic variation in proanthocyanidin biosynthesis pathway genes in soybean (Glycine spp.)

Abstract: We detected major differences in the transcriptional levels of genes involved in the biosynthesis of proanthocyanidin and anthocyanin among genotypes beginning at the early stage of seed development. The results of the present study provide insights into the underlying genetic variation in proanthocyanidin biosynthesis among soybean genotypes. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…Brown soybeans have only PAs, but no anthocyanins [ 38 , 75 , 83 , 84 ]. IT109098—a G. max genotype with a brown seed coat—has been reported to have PA levels as high as those of G. soja [ 18 ]. It has been reported that the differences in the expression levels of genes encoding delphinidin 3- O -glucoside 2″- O -glucosyltransferases and ANR result in variations in the levels of anthocyanin and PA between the three genotypes with different seed coat colors: cultivated soybean (yellow), landrace (brown), and wild soybean (black).…”
Section: Biosynthetic Pathways Of Pas and Anthocyaninsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown soybeans have only PAs, but no anthocyanins [ 38 , 75 , 83 , 84 ]. IT109098—a G. max genotype with a brown seed coat—has been reported to have PA levels as high as those of G. soja [ 18 ]. It has been reported that the differences in the expression levels of genes encoding delphinidin 3- O -glucoside 2″- O -glucosyltransferases and ANR result in variations in the levels of anthocyanin and PA between the three genotypes with different seed coat colors: cultivated soybean (yellow), landrace (brown), and wild soybean (black).…”
Section: Biosynthetic Pathways Of Pas and Anthocyaninsmentioning
confidence: 99%
“…Barks of common cinnamons are abundant with PAs, used as a fold medicine or supplement [ 17 ]. In soybeans, a cultivar containing high PA levels has been used as an ingredient for cosmetic products [ 18 ]. In grapes, because PAs are intensively accumulated in their seeds, seed oil products have been used as supplements for health promotion [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that anthocyanidins are either immediately modified by glycosylation to give anthocyanins by anthocyanidin 3‐o‐glycosyltransferases or are reduced to generate flavan‐3‐ols (such as epicatechin) by ANR for PA biosynthesis (Kovinich, Saleem, Arnason, & Miki, 2012; Li et al., 2016). Inverse relationships between the expression of ANR and anthocyanidin 3‐o‐glycosyltransferase in soybean has also been proposed to switch anthocyanidins into either PA or anthocyanin biosynthetic pathways (Ha et al., 2018). Mattivi, Vrhovsek, Masuero, and Trainotti (2008) also reported a decreasing trend in PA levels in the skin of Nebboilo and Barbera seeds during ripening.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from saponins, other compounds such as soy isoflavones, polyphenols, flavonoids, proanthocyanidins, and phenolic acids have also been analyzed in large-scale wild soybean collections in Korea as well as in wild soybeans from other natural habitats. These studies identified unique germplasm accessions with higher amounts of these beneficial/desirable secondary metabolites that will be an important resource for future breeding (Ha et al 2018;Nawaz et al 2018;Tsukamoto et al 2018). In additional to beneficial metabolites, trace harmful metabolites such as raffinose are also found in soybean.…”
Section: Progress On Soybean Molecular Breeding In the Republic Of Koreamentioning
confidence: 99%